Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Development of soil health benchmarks for managed and semi-natural landscapes - Christopher J. Feeney; David A. Robinson; Aidan M. Keith; Audric Vigier; Laura Bentley; Richard P. Smith; Angus Garbutt; Lindsay C. Maskell; Lisa Norton; Claire M. Wood; B. Jack Cosby; Bridget A. Emmett (Science of The Total Environment, 2023)

Using citizen science to estimate surficial soil Blue Carbon stocks in Great British saltmarshes - Craig Smeaton; Annette Burden; Paulina Ruranska; Cai J. T. Ladd; Angus Garbutt; Laurence Jones; Lucy McMahon; Lucy C. Miller; Martin W. Skov; William E. N. Austin (Frontiers in Marine Science, 2022)
A new saltmarsh soil dataset comprising of geochemical and physical property data from 752 soil samples collected through a sampling program supported by citizen scientists has been brought together with existing data to make the first national estimates of the surficial (top 10 cm) soil OC stock for Great British (GB) saltmarshes. To allow the inclusion of secondary data in the soil stock estimate a new bespoke organic matter to organic carbon conversion for GB saltmarsh soil was developed allowing organic matter data measured using loss-on-ignition to be convert to organic carbon content. The total GB surficial soil OC stock is 2.320 ± 0.470 Mt; English saltmarshes hold 1.601 ± 0.426 Mt OC, Scottish saltmarshes hold 0.368 ± 0.091 Mt OC, and Welsh saltmarshes hold 0.351 ± 0.082 Mt OC. The stocks were calculated within a Markov Chain Monte Carlo framework allowing robust uncertainty estimates to be derived for the first time. Spatial mapping tools are available to accompany these stock estimates at individual saltmarsh habitats throughout GB. This data will aid in the protection and management of saltmarshes and represents the first steps towards the inclusion of saltmarsh OC in the national inventory accounting of blue carbon ecosystems.

European salt marshes: ecology and conservation in a changing world - Angus Garbutt; Alma de Groot; Chris Smit; Julien Pétillon (Journal of Coastal Conservation, 2017)

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Inundation Frequency Determines the Post-Pioneer Successional Pathway in a Newly Created Salt Marsh - Julien Pétillon; Reza Erfanzadeh; Angus Garbutt; Jean-Pierre Maelfait; Maurice Hoffmann (Wetlands, 2010)

Factors affecting the success of early salt-marsh colonizers: seed availability rather than site suitability and dispersal traits - Reza Erfanzadeh; Angus Garbutt; Julien Pétillon; Jean-Pierre Maelfait; Maurice Hoffmann (Plant Ecology, 2010)